AYAT KAUNIYAH DAN SAINS MODERN: ANALISIS TAFSIR ILMI TERHADAP AIR, LANGIT-BUMI, DAN PERGANTIAN SIANG-MALAM DALAM KARYA ZAGHLOUL EL-NAGGAR - Afro Zakiyah; Faliha Syaifi Jannah; Aulia Ali Irsyad; Puspita Fajriany; Andi Rosa (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This article is an in-depth study of Zaghlul El-Naggar's work on the verses of the cosmos which is an important contribution to contemporary scholarly interpretation that seeks to harmonize the interpretation of the Qur'an with the latest scientific discoveries. The main purpose of this research is to analyze the three basic dimensions of the book, namely its structural structure, the essence of its interpretation, and the methodology used on the theme of water, earth, and day-night alternation. This study applies a qualitative method with a type of literature research, which focuses on the analysis of written sources related to the research topic. The findings of this study show that each kauniyah theme discussed by El-Naggar has a depth of meaning that goes beyond just scientific explanations. On the theme of water, the Qur'an not only affirms the biological role of water, but also places it as a fundamental element in the entire system of life that God created. Likewise, the theme of the creation of heaven and earth and the alternation of day and night, both of which are understood not only as ordinary natural phenomena, but as signs (verses) of Allah's power that must encourage humans to think critically, study the universe, and get closer to the Creator.